Influence of plant density and growth habit of common bean on leaf area development and N accumulation - Clavijo Michelangeli, José A.; Ricaurte Oyola, José Jaumer; Sinclair, Thomas R.; Rao, Idupulapati M.; Beebe, Stephen E. (Informa UK Limited, 2019)
Crop yield requires leaf area to intercept solar radiation and to undertake photosynthesis, both of which depend on nitrogen (N) accumulation. Further, the amount of accumulated plant N at the beginning of seed fill serves as the reservoir for N required in synthesizing the proteins in developing seeds. For common bean (Phaseolus vulgaris L.), resolution of the basic characteristics limiting production is challenging because of variation in plant growth-habit and in wide-ranging plant spacing. Field experiments were undertaken at two low-latitude locations with three plant growth-habit types and six plant densities to measure canopy leaf area and leaf N accumulation at the beginning of seed fill. Plant spacing of 20 plants m−2 or more was sufficient to result in equal leaf area and N accumulation for all six plant genotypes at each location. However, the low-altitude, higher-temperature location had lower accumulated leaf N and yield than the high-altitude, cooler-temperature location. These results indicate attention needs to be given to physiological or agronomic approaches to overcome the negative impact of high temperature on N accumulation by common bean.